Mobilizing MSMEs Toward a Sustainable Economy: The Role of Community Service from the Perspectives of Green Economy and Entrepreneurial Innovation - Sutrisno; Dwi Prastiyo Hadi; Hizbul Khootimah Az Zaakiyyah (PT. LITERASI SAINS NUSANTARA, 2026)
The transformation toward a sustainable economy requires the active involvement of MSMEs as key actors in local economic development. However, limitations in internal capacity, low levels of environmental literacy, and a lack of entrepreneurial innovation remain major challenges in encouraging MSMEs to adopt sustainability principles. This study aims to expand and enrich scientific references related to community service and its role in mobilizing MSMEs toward a sustainable economy through the perspectives of the green economy and entrepreneurial innovation. The research method employed is a literature review with a qualitative approach and descriptive analysis. Data were obtained from Google Scholar and selected credible websites published between 2019 and 2026. From an initial identification of 50 articles, a rigorous selection process resulted in 32 relevant articles for analysis. The findings indicate that community service plays a strategic role as an instrument of empowerment, knowledge transfer, and innovation catalyst that encourages MSMEs to adopt environmentally friendly practices and sustainable business models. This study emphasizes that the integration of community service with green economy principles and entrepreneurial innovation can strengthen MSME competitiveness while supporting the achievement of sustainable development goals.